Parenting Practices on Social Media in The Digital Era: A Systematic Literature Review - Matang, Matang; Rahmad, Abdul; Murthada, Murthada; Raya, Aqshal Arlian; Astina, Syahputra Perdana (THUFULA, 2025)
This study aims to analyse parenting styles and practices on social media in the digital era. The research focuses on how social media influences parent–child interactions, the forms of parenting practices that emerge, and the positive and negative impacts involved. The method used is a systematic literature review, examining 170 articles from Google Scholar published in the last five years. After selection based on thematic relevance, quality, and relation to the research topic, 45 articles were further analysed. The findings show that parenting practices have transformed alongside the widespread use of social media. Social media has become a space for communication and interaction between parents and children, for sharing experiences, receiving support, and engaging with parenting content. However, social media also brings challenges such as sharenting, mom shaming, child privacy violations, digital addiction, and cyberbullying among adolescents. On the other hand, parents’ digital literacy, healthy interpersonal communication, and support for moral, religious, and community values are key factors in optimising parenting practices in the digital era. This study concludes that parenting on social media is ambivalent. Opportunities for strengthening parenting, as well as risks to anticipate through adaptive, wise, and digital-literate parenting.